2008
DOI: 10.1149/1.2982567
|View full text |Cite
|
Sign up to set email alerts
|

High Catalytic Activity of Palladium for Metal-Enhanced Hydrofluoric Acid Etching of Silicon

Abstract: Metal-enhanced HF etching of Si is an electroless method to produce porous Si. Such etching generally uses not only metal-modified Si but also an oxidizing agent, such as hydrogen peroxide. Pd exhibits high activity for enhancing the HF etching of Si without an oxidizing agent, even under dissolved oxygen free and dark conditions. Electrolessly deposited Pd particles on n-Si enhance the HF etching of Si, but produce no porous layer. Patterned Pd films localize the etching under and the boundary of the Pd depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…15,18 In this paper, we describe the unique behavior of Pd on HF etching of Si and micropattern formation. 19…”
mentioning
confidence: 99%
“…15,18 In this paper, we describe the unique behavior of Pd on HF etching of Si and micropattern formation. 19…”
mentioning
confidence: 99%
“…Pt formed both a porous layer and helical etch track pores on 10 Ω·cm p-type wafers; the latter was attributed to the multifaceted crystalline shape of the Pt particles. Pd was found to be more convoluted than others as it catalyzed etching even without an oxidant and resulted in electropolishing of Si. HL-MACE with Cu never produced defined etch track pores , and Si NWs, except in the case of electrochemical etching under applied bias . This is due to the low electronegativity and reduction potential of Cu compared to those of other metals, which prevents efficient deposition and leads to enhanced dissolution during etching.…”
Section: Introductionmentioning
confidence: 99%
“…This deposition reaction consists of a local cathodic formation of metal and a local anodic dissolution of Si. This deposition method has been studied for application of the defect detection of Si wafers (5,6) and catalytic-fine-metal-particleformation for photoelectrochemical solar cells (4, 7-10), metal-particle-assisted HF etching of Si (7,8,(10)(11)(12), and autocatalytic electroless plating (12)(13)(14). We previously reported that the particle density of metals varied widely from 10 6 (Pt) to 10 11 (Au) cm -2 , depending on the kind of metal (Pt, Ag, Au, Cu, Pd, and Rh) (3).…”
Section: Introductionmentioning
confidence: 99%